Multicentre post-infarction trial of propranolol in 49 hospitals in the United Kingdom, Italy, and Yugoslavia. Issue 1 (July 1980) - Baber, N S; Evans, D W; Howitt, G; Thomas, M; Wilson, T; Lewis, J A; Dawes, P M; Handler, K; Tuson, R
Abstract : A multicentre study of survivors of an anterior myocardial infarction is reported. The trial consisted of 720 patients and was a double-blind, placebo-controlled study with propranolol 40 mg three times a day. Trial entry was at two to 14 days (mean 8.5 days) and follow-up at one, three, and in most centres, six and nine months. The trial was designed to detect a 50 per cent reduction in mortality and this was not shown. The non-fatal reinfarction rate was similar in both groups. Subgroup analysis identified several prognostic risk factors for death, none of which interacted with treatment.